Reception Of English Law In Malaysia: Lee Kee Chong V Empat Nombor Ekor (N.S.) Sdn. Berhad - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2018)
Reception Of English Law In Malaysia: Lee Kee Chong V Empat Nombor Ekor (N.S.) Sdn. Berhad